Research Progress on Hydrogen Energy Utilization in Low-carbon Building - ZHU Xinrong; WANG Yongchao; YANG liu (工程科学与技术)
The application of renewable energy in the building sector can greatly reduce carbon emissions. However, due to the intermittent nature of renewable energy supply, it cannot meet the energy demands of buildings at all times. In recent years, extensive research has been conducted on the application of hydrogen energy in buildings, both domestically and internationally. Firstly, the various stages of hydrogen energy—from production to application in buildings—were reviewed. Current mainstream methods of hydrogen production, storage, transportation, and utilization in buildings, as well as future development trends, were summarized. The results show that hydrogen production via electrolysis of water using renewable energy is still in its early stages and accounts for only a small share of total hydrogen production. However, with further reductions in the cost of wind and solar power generation, and improvements in long-distance hydrogen storage and transportation, this method may become a primary means of hydrogen production in the future. Proton exchange membrane electrolyzers show good potential for absorbing fluctuating wind and photovoltaic power. Liquid hydrogen transport by vehicles and ships, pure hydrogen pipelines, and natural gas pipelines blended with hydrogen are likely to be the main forms of hydrogen transport moving forward. Currently, hydrogen is used in buildings in several ways: blending with natural gas, using pure hydrogen, converting hydrogen to methane, and applying hydrogen fuel cell cogeneration systems. Secondly, the specific forms of building hydrogen utilization systems were categorized, including combinations of photovoltaic hydrogen storage with solar thermal systems, ground source heat pumps, hydrogen fuel vehicles, batteries, and fossil fuel systems. The structure and operational strategies of these systems were outlined. Practical cases of hydrogen application in buildings—spanning residential buildings, office buildings, building clusters, and communities—were collected and described, along with typical examples highlighting the modes and key parameters of hydrogen utilization. The cost conditions related to photovoltaic hydrogen production, hydrogen storage and transport, and hydrogen fuel cells were also detailed. The results indicate that although photovoltaic hydrogen production is still more expensive than hydrogen production from coke oven gas, it shows competitiveness compared to other methods such as natural gas reforming, methanol-based production, and ammonia decomposition. From a carbon emission perspective, photovoltaic hydrogen production holds significant advantages over coke oven gas methods in the long term. At present, most hydrogen-related equipment in China relies on imports. High costs, particularly for hydrogen fuel cells, remain a key obstacle to the broader promotion of hydrogen energy. Finally, the application of hydrogen energy in buildings in China was discussed, and future development directions were summarized, including how to match building load characteristics in various scenarios with different energy storage systems; evaluating the comprehensive performance of hydrogen energy systems in buildings; and achieving breakthroughs in key technologies such as renewable hydrogen production, fuel cells, and combined heat and power generation to reduce the cost of hydrogen utilization. These research findings can serve as a reference for promoting and applying hydrogen energy in Chinese buildings.